Integrated Molecular and Clinical Analysis of 1,000 Pediatric Low-Grade Gliomas - Ryall, Scott; Zapotocky, Michal; Fukuoka, Kohei; Nobre, Liana; Guerreiro Stucklin, Ana; Bennett, Julie; Siddaway, Robert; Li, Christopher; Pajovic, Sanja; Arnoldo, Anthony; Kowalski, Paul E; Johnson, Monique; et al. (Cancer cell, 2020)
Pediatric low-grade gliomas (pLGG) are frequently driven by genetic alterations in the RAS-mitogen-activated protein kinase (RAS/MAPK) pathway yet show unexplained variability in their clinical outcome. To address this, we characterized a cohort of >1,000 clinically annotated pLGG. Eighty-four percent of cases harbored a driver alteration, while those without an identified alteration also often exhibited upregulation of the RAS/MAPK pathway. pLGG could be broadly classified based on their alteration type. Rearrangement-driven tumors were diagnosed at a younger age, enriched for WHO grade I histology, infrequently progressed, and rarely resulted in death as compared with SNV-driven tumors. Further sub-classification of clinical-molecular correlates stratified pLGG into risk categories. These data highlight the biological and clinical differences between pLGG subtypes and opens avenues for future treatment refinement.
Keywords: Female; nádory mozku; Glioma; novorozenec; Brain Neoplasms; regulace genové exprese u nádorů; Adolescent; Oncogene Proteins, Fusion; neurofibromin 1; kohortové studie; mužské pohlaví; mutace; variabilita počtu kopií segmentů DNA; Gene Expression Profiling; Biomarkers, Tumor; DNA Copy Number Variations; kojenec; Humans; Infant; Child, Preschool; Gene Rearrangement; Mitogen-Activated Protein Kinases; nádorové biomarkery; mitogenem aktivované proteinkinasy; lidé; ras proteiny; protoonkogenní proteiny B-raf; ras Proteins; Cohort Studies; ženské pohlaví; Child; Neurofibromin 1; Gene Expression Regulation, Neoplastic; Mutation; předškolní dítě; genová přestavba; dítě; stanovení celkové genové exprese; Infant, Newborn; gliom; Male; mladiství; fúzní onkogenní proteiny; Proto-Oncogene Proteins B-raf